The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3920/bm2015.0109
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of Lactobacillus brevis K65 on RAW 264.7 cells and in mice with dextran sulphate sodium-induced ulcerative colitis

Abstract: Lactic acid bacteria (LAB) with anti-inflammatory effects may be beneficial to the prevention or treatment for inflammation-related diseases, such as inflammatory bowel diseases. In an in vitro assay, heat-killed Lactobacillus brevis K65 (K65) reduced lipopolysaccharide-induced production of nitric oxide, tumour necrosis factor (TNF)-α and prostaglandin E2 in RAW 264.7 cells. In RAW 264.7 cells stably expressing an ind=ucible nitric oxide synthase (iNOS) reporter, viable K65 showed greater inhibition of iNOS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Firstly, the control group was given distilled water, the DDS-induced colitis group (DSS) was received 3.5% (w/v) DSS (36–50 kDa, MP Biomedicals Ltd., Santa Ana, U.S.A.) in drinking water for 7 days. Then, the low-dose (LD) group and the high-dose (HD) group were given 1 × 10 9 or 1 × 10 10 CFU/mL L. plantarum L15 (1 mL/100 g body weight) ( 26 , 27 ) by oral gavage once daily for a period of 28 days, respectively. Bacteria were harvested by centrifugation at 5,000 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the control group was given distilled water, the DDS-induced colitis group (DSS) was received 3.5% (w/v) DSS (36–50 kDa, MP Biomedicals Ltd., Santa Ana, U.S.A.) in drinking water for 7 days. Then, the low-dose (LD) group and the high-dose (HD) group were given 1 × 10 9 or 1 × 10 10 CFU/mL L. plantarum L15 (1 mL/100 g body weight) ( 26 , 27 ) by oral gavage once daily for a period of 28 days, respectively. Bacteria were harvested by centrifugation at 5,000 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…in terms of Lactobacillus members of the Bacilli class, orally administered lP-K68 ameliorated dSS-induced colitis in BalB/c mice by reducing the production of pro-inflammatory cytokines such as TNF-α, il-1β, and il-6 (12). Lactobacillus brevis K65 reduced the levels of the pro-inflammatory cytokines TNF-α, il-6, and il-1β (25). Lactobacillus reuteri F-9-35 prevented dSS-induced colitis by inhibiting the expression of several pro-inflammatory genes, namely those for TnF-α, cyclooxygenase-2, and il-6 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus and Bifidobacterium, both of which have probiotic characteristics, play a pivotal role in the intestinal environment by preventing pathogen colonization and maintaining normal mucosal immunity. increased numbers of Lactobacillus and Bifidobacterium lead to downregulation of the gene expression of pro-inflammatory cytokines such as TNF-α, il-6, and il-1β (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Thus, as a result of changing the composition of the intestinal microflora, heat-killed 06CC2 may indirectly prevent colitis.…”
Section: Discussionmentioning
confidence: 99%
“…2015). Studies have reported that Lactobacillus brevis K65 and Lactobacillus paracasei ameliorated DSS-induced ulcerative colitis in mice through the suppression of TNF-α expression (Liu et al, 2016;Pan et al, 2014). Lactobacillus brevis G-101 attenuated colitis by inhibiting TNF-α and IL-1β expression, and by increasing IL-10 expression (Jang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%